Stimulasi Kreativitas Anak Usia Dini Melalui Art and Craft di TK Darussalam Semarang - Puspita Puji Rahayu; Menik Tetha Agustina; Qurnia Fitriyatinur (Institut Teknologi dan Bisnis Semarang, 2024)
Creativity is an aspect of every individual that is very important to stimulate from an early age. Early childhood is a time when children's development is very rapid, including the development of creativity, especially because at that time children have the characteristics of high curiosity as one of the provisions for their creativity. Based on this, early childhood education services should provide activities that can stimulate the development of children's creativity. This activity aims to stimulate children's creativity, namely art and craft activities carried out by Kindergarten Darussalam Semarang. The method used in carrying out this activity is practice. The results obtained showed that the arts and craft activities carried out consisted of several activities such as drawing and forming origami paper. This activity can stimulate children to be creative according to their wishes and create masterpieces.